TRANSGENDER: GEREJA YANG MENCARI DAN MEMULIHKAN - Hutabarat, Samuel; Silalahi, Frans (Fidei: Jurnal Teologi Sistematika dan Praktika, 2025)
Transgender is an individual who is interested in living as the opposite gender, regardless of whether they want to take do it as far as dressing in the opposite gender in daily life or undergoing gender reassignment surgery. Transgender is a lifestyle that demands recognition and acceptance from society, including the church. The church must focus on God's teaching that everyone, including transgender, must be served and saved. The research uses qualitative research, focusing on a descriptive approach to outline and explain the issues clearly, and in-depth analysis through critical interpretation of the literature. The analysis of the literature materials is conducted by selecting relevant materials related to the researched topic to delve into the subjects associated with transgender, the church, trauma, and Harvest Theology. This research aims to: (1) examine the Biblical view on transgender; (2) how the church can holistically serve transgender individuals; (3) what evangelistic methods are suitable for reaching out to transgender people; (4) how the church can foster strong and healthy families under God's authority. The results of the study indicate that the Bible clearly states that being transgender is wrong, Harvest Theology helps the church grow by encouraging evangelism towards transgender individuals, the church must assist transgender individuals and congregants in healing from trauma, and work on family restoration as a reflection of God's perfect love. AbstrakTransgender adalah individu yang tertarik hidup sebagai lawan jenis, terlepas dari apakah dijalankan hanya sebatas berpakaian lawan jenis dalam kehidupan sehari atau melakukan operasi ganti kelamin. Transgender adalah suatu gaya hidup yang menuntut pengakuan dan penerimaan dari masyarakat, termasuk gereja. Gereja harus fokus pada pengajaran Tuhan bahwa semua orang, termasuk transgender, harus dilayani dan diselamatkan. Penelitian menggunakan penelitian kualitatif (qualitative research), dengan fokus pada pendekatan deskriptif untuk menguraikan dan menjelaskan masalah sehingga menjadi jelas dan pendekatan analisis mendalam melalui interpretasi kritis terhadap literatur. Analisa terhadap materi literatur dilakukan dengan memilih bahan-bahan yang relevan dengan topik yang diteliti untuk mendalami materi yang terkait dengan transgender, gereja, trauma, dan Harvest Theology. Penelitian ini bertujuan untuk; (1) mengkaji pandangan Alkitab terhadap transgender; (2) bagaimana gereja melayani transgender secara holistik; (3) metode penginjilan apa yang cocok untuk menginjil transgender; (4) bagaimana gereja membentuk keluarga yang kuat dan sehat dibawah otoritas Tuhan. Hasil penelitian adalah Alkitab tegas menyatakan transgender adalah salah, Harvest Theology membantu gereja bertumbuh dengan mendorong penginjilan terhadap transgender, gereja harus membantu transgender dan jemaat untuk sembuh dari trauma, dan pemulihan keluarga sebagai citra kasih Allah yang sempurna.